High-strength high-temperature titanium alloy and preparation method

By adding B and Si elements to high-temperature titanium alloys, refine the grains and improve the microtexture, the problems of oxide layer failure and low room temperature strength of high-temperature titanium alloys are solved, and high strength and excellent oxidation resistance are achieved.

CN119614945APending Publication Date: 2025-03-14XI AN JIAOTONG UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510063085.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing high-temperature titanium alloys above 700°C will damage the surface oxide layer, resulting in a decrease in mechanical properties and a low room temperature strength, which limits its use temperature.

Method used

Through the coordinated refinement of grains by B and Si elements, pinning dislocations, improving the microtexture of high-temperature titanium alloy, and forming a high-temperature titanium alloy with high strength. The specific method includes adding 4.7~6.5% Al, 4.0~6.0% Sn, 2.5~3.5% Nb, 0.5~2.0% Mo, 0.2~0.5% Si, 0.05~0.15% B to the alloy, and the balance is Ti, and undergoing multiple smelting, homogenization treatment, hot rolling and heat treatment.

Benefits of technology

The high strength and excellent oxidation resistance of high-temperature titanium alloy are achieved, the room temperature strength is improved, and the use temperature of the alloy is extended, solving the problem of degradation of the mechanical properties of existing high-temperature titanium alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614945A_ABST
    Figure CN119614945A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and high-temperature titanium alloy and a preparation method, and belongs to the technical field of alloy materials, the high-strength and high-temperature titanium alloy comprises, by mass, 4.7%-6.5% of Al, 4.0%-6.0% of Sn, 2.5%-3.5% of Nb, 0.5%-2.0% of Mo, 0.2%-0.5% of Si, 0.05%-0.15% of B and the balance Ti and inevitable impurity elements; the yield strength of the high-temperature titanium alloy is larger than 1200 MPa, and meanwhile the ductility of the high-temperature titanium alloy is 11.38%. And the alloy has the tensile strength exceeding 1400 MPa when martensite is not subjected to heat treatment and complete decomposition, still has the ductility of 5%, and can further meet the requirement of current aerospace for the high strength of the high-temperature titanium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy materials, and in particular to a high-strength and high-temperature titanium alloy and a preparation method thereof. Background Art

[0002] High-temperature titanium alloy refers to a disordered solid solution strengthened titanium alloy with an operating temperature of 300°C or above. High-temperature titanium alloys are widely used in the aerospace field, especially in aero-engines, because of their high specific strength, plasticity, and creep resistance. As the speed of aircraft continues to increase, the requirements for the working temperature and mechanical properties of high-temperature titanium alloys are getting higher and higher. The most mature Ti-Al-Sn-Zr-Mo-Si high-temperature titanium alloy currently studied, the addition of Zr element improves the thermal strength of high-temperature titanium alloys, effectively matching thermal strength and thermal stability, but it will destroy the surface oxide layer of high-temperature titanium alloys above 700°C, causing the mechanical properties to seriously decrease. Therefore, in order to break through the bottleneck of high-temperature titanium alloys, a new high-temperature titanium alloy composition system must be designed.

[0003] In addition, high-temperature titanium alloys generally have the problem of low room temperature strength, and there is a strong correlation between room temperature strength and high temperature strength. For example, the yield strength of Ti6242 at room temperature is 890~940 MPa (tensile strength is 970-1030MPa), and the yield strength of IMI834 at room temperature is 930~980MPa (tensile strength is 1040-1090MPa). These problems have caused the use temperature of high-temperature titanium alloys to stagnate at the bottleneck of 600℃.

[0004] In order to further meet the needs of practical applications, achieve lightweight aerospace, break through the current operating temperature bottleneck of high-temperature titanium alloys, and develop a new system of high-strength and high-temperature titanium alloys, it has become a key issue that needs to be solved urgently. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a high-strength and high-temperature titanium alloy and a preparation method thereof, wherein B and Si elements synergistically refine grains, pin dislocations, and improve microtexture in the high-temperature titanium alloy to form a high-strength high-temperature titanium alloy.

[0006] The present invention is achieved through the following technical solutions: A high-strength and high-temperature titanium alloy comprises, by mass percentage, 4.7-6.5% Al, 4.0-6.0% Sn, 2.5-3.5% Nb, 0.5-2.0% Mo, 0.2-0.5% Si, 0.05-0.15% B, and the balance is Ti and unavoidable impurity elements.

[0007] Preferably, the Mo is a titanium-molybdenum intermetallic compound.

[0008] Preferably, the microstructure of the high-strength and high-temperature titanium alloy contains dispersed TiB particles in the form of fine needles.

[0009] A method for preparing a high-strength and high-temperature titanium alloy comprises the following steps: Step 1, mix the elements evenly according to mass percentage; Step 2, melting the alloy mixture formed in step 1 multiple times, and obtaining an ingot after cooling; Step 3, homogenizing the ingot; Step 4, hot rolling the ingot obtained in step 3 from the single-phase region to the dual-phase region for multiple passes, with a cumulative rolling deformation of 75-90%, and cooling to room temperature after rolling; Step 5: heat-treating the hot-rolled plate in a two-phase region to obtain a high-strength and high-temperature titanium alloy.

[0010] The heat treatment includes solution treatment and aging treatment: The temperature of the solution treatment is 960-1020° C., the solution treatment time is 1-2.5 hours, the temperature of the aging treatment is 600-710° C., and the aging time is 3-6 hours.

[0011] Preferably, the specific method of smelting in step 2 is as follows: During the smelting process, the induced current is 550-700A, the current frequency is 20-25KHz, and the alloy mixture is kept for 3-5 minutes after being completely melted. After cooling, an ingot is obtained, and then the ingot is smelted multiple times.

[0012] Preferably, the homogenization method in step 3 is as follows: The ingot is kept at 1050~1200℃ for 1~3h.

[0013] Preferably, the method of single-phase hot rolling in step 4 is as follows: The initial rolling temperature is 20~40℃ above the phase transformation point. The steel is kept warm for 30min before rolling and returned to the furnace for insulation after each rolling pass for 1~3min. The total rolling deformation is 40~60%. The steel is cooled to room temperature after hot rolling.

[0014] Preferably, the method of dual-phase hot rolling is as follows: The rolling temperature is 30~50 ℃ below the phase transformation point, the rolling termination temperature is in the two-phase region, the furnace is returned to the furnace for insulation after each rolling pass, the insulation time is 1~3 min, and the rolling deformation is 60~90%.

[0015] Preferably, the cooling method in step 4 is water cooling.

[0016] The invention discloses an application of a high-strength and high-temperature titanium alloy in automobile and aviation engines.

[0017] Compared with the prior art, the present invention has the following beneficial technical effects: The application provides a high-strength high-temperature titanium alloy. The composite effect of Al, Sn, Nb, Mo, Si, and B improves the oxidation resistance of the high-temperature titanium alloy and forms a dense oxide layer on the surface. The B and Si elements synergistically refine the grains, pin dislocations, and improve the micro-texture in the high-temperature titanium alloy to obtain a high-strength high-temperature titanium alloy. Compared with the existing high-temperature titanium alloy, it has excellent room temperature strength. Compared with the intermetallic compound TiAl, Ti 2 AlNb has better ductility and achieves excellent strength-plasticity matching; it solves the problem of low room temperature strength of existing high-temperature titanium alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 This is a 30un microstructure diagram of the Ti-Al-Sn-Nb-Mo-Si-B titanium alloy after hot rolling of the present invention; Figure 2 This is a 3un microstructure diagram of the Ti-Al-Sn-Nb-Mo-Si-B titanium alloy after hot rolling of the present invention; Figure 3 This is the microstructure of the Ti-Al-Sn-Nb-Mo-Si-B titanium alloy after heat treatment in Example 1 of the present invention; Figure 4 This is the microstructure of the Ti-Al-Sn-Nb-Mo-Si-B titanium alloy after heat treatment in Example 2 of the present invention; Figure 5 This is the microstructure of the Ti-Al-Sn-Nb-Mo-Si-B titanium alloy after heat treatment in Example 3 of the present invention; Figure 6 This is the microstructure of the Ti-Al-Sn-Nb-Mo-Si-B titanium alloy after heat treatment in Example 4 of the present invention; Figure 7 The tensile performance curve of the Ti-Al-Sn-Nb-Mo-Si-B titanium alloy of the present invention after hot rolling and heat treatment process; Figure 8 The performance of the Ti-Al-Sn-Nb-Mo-Si-B high-strength high-temperature titanium alloy of the present invention is comparable to that of the existing near-α-type high-temperature titanium alloy and Ti 2Comparison chart of properties of AlNb, TiAl intermetallic compound titanium alloys. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.

[0021] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0022] A high-strength and high-temperature titanium alloy comprises, by mass percentage, 4.7-6.5% Al, 4.0-6.0% Sn, 2.5-3.5% Nb, 0.5-2.0% Mo, 0.2-0.5% Si, 0.05-0.15% B, and the balance is Ti and unavoidable impurity elements.

[0023] The above Ti, Al, Sn, Si and B are high-purity titanium, high-purity aluminum, high-purity tin, high-purity silicon and high-purity boron powders. Nb and Mo are high-purity titanium-niobium and titanium-molybdenum intermetallic compounds to ensure uniform composition of the ingot during smelting.

[0024] The microstructure of the near-α-type high-strength and high-temperature titanium alloy contains dispersed TiB particles in the form of fine needles.

[0025] The high-strength and high-temperature titanium alloy selectively adds Al, Sn, Nb, Mo, Si and B elements to the alloy composition, and uses Nb and Mo alloy elements to stabilize and strengthen the β phase; similarly, while adding the Al element to strengthen the α phase, the neutral element Sn is added to strengthen the α phase and inhibit the formation of the ω phase; the B element is added to form TiB, and fine TiB particles are formed through rolling, which provide a heterogeneous nucleation core when the β phase is transformed into the α phase, play a role in refining the α grains and reducing the microtexture appearing in the titanium alloy, and improve the performance of the titanium alloy.

[0026] The high temperature titanium alloy is used in the aerospace field, such as aircraft engines and aircraft.

[0027] Based on the above high-strength and high-temperature titanium alloy, the present application also provides a method for preparing the high-strength and high-temperature titanium alloy, comprising the following steps: Step 1, high purity titanium, high purity aluminum, high purity tin, high purity silicon, high purity boron powder, high purity titanium niobium, titanium molybdenum intermetallic compound, according to the above mass percentage, are mixed uniformly and loaded into the furnace in bulk; The mass percentage of each element is: 4.7~6.5% Al, 4.0~6.0% Sn, 2.5~3.5% Nb, 0.5~2.0% Mo, 0.2~0.5% Si, 0.05~0.15% B, and the balance is Ti and unavoidable impurity elements.

[0028] Step 2: Under an argon atmosphere, the alloy mixture formed in step 1 is smelted multiple times, and an ingot is obtained after cooling, as follows: A vacuum non-consumable melting furnace is used for smelting. Argon gas is introduced during the smelting process. The induced current is 500-700A and the current frequency is 20-25KHz. After the current is slowly increased to the maximum value, electromagnetic stirring is turned on to ensure uniform alloy composition. After the alloy is completely melted, it is maintained for 3-5 minutes. After cooling, an ingot is obtained, and then the ingot is turned over for further smelting. The smelting number is ≥7, and an ingot is obtained after the smelting is completed.

[0029] Step 3: subject the ingot to high temperature homogenization treatment, the heat treatment temperature is 1050~1200℃, and the time is 1~3h.

[0030] Step 4: hot rolling the homogenized ingot from the single-phase region to the dual-phase region, and cooling to room temperature after rolling.

[0031] For single-phase hot rolling, the initial rolling temperature is designed to be 20~40℃ above the phase transition point. The specific rolling process is as follows: 30 minutes of heat preservation before rolling, 1~3 minutes of heat preservation after each rolling pass, and the total rolling deformation is 40~60%. After hot rolling, it is cooled to room temperature.

[0032] The rolling temperature of the two-phase hot rolling is 30~50℃ below the phase change point. The specific rolling process is as follows: the rolling end temperature is the two-phase region, the steel is returned to the furnace for heat preservation after each rolling pass, the heat preservation time is 1~3 min, and the rolling deformation is 60~90%.

[0033] The above cooling method is water cooling.

[0034] Step 5: Perform aging treatment on the hot-rolled plate in the two-phase region to obtain a high-strength and high-temperature titanium alloy. The details are as follows: the solution treatment temperature is 960-1020°C, the solution treatment time is 1~2.5h, the aging treatment temperature is 600~710°C, and the aging time is 3~6h.

[0035] Example 1 A method for preparing a high-strength and high-temperature titanium alloy comprises the following steps: Step 1. In terms of mass percentage, the mass percentage of each element is: 6% Al, 4.84% Sn, 3% Nb, 0.5% Mo, 0.35% Si, 0.1% B, and the remainder is Ti and unavoidable impurity elements.

[0036] Step 2: Use a vacuum non-consumable melting furnace for smelting. During the smelting process, argon gas is introduced. The induced current is slowly increased from the starting current to 500A, and the current frequency is 25KHz. After the alloy is completely melted, the current is continued to be increased to 650A. Turn on the electromagnetic stirring and keep it for 2 minutes to ensure uniform smelting. After turning off the electromagnetic stirring, slowly reduce the current until it reaches the minimum value. After cooling, obtain an ingot, then turn the ingot over and continue smelting. The smelting number is 7, and the ingot is obtained after the smelting is completed.

[0037] Step 3: subject the ingot to high temperature homogenization heat treatment at a temperature of 1100° C. for 1 h.

[0038] Step 4: Hot-roll the homogenized ingot in the single-phase region. The hot-rolling temperature is 20°C higher than the phase transformation point. After each hot-rolling pass, return to the furnace for heat preservation. The heat preservation time is 1.5 minutes. The rolling deformation is 50%, and the deformation of a single rolling pass is 7% to 10%. Then the alloy is heated to the two-phase region, that is, 50°C below the phase transformation point, and the total rolling deformation is 85%. After hot rolling, it is water-cooled to room temperature. Its hot-rolled microstructure is as follows: Figure 1 and Figure 2 As shown, β grains and equiaxed αp grains.

[0039] Step 5: subject the hot-rolled plate to solution treatment and aging treatment to obtain a near-α titanium alloy. The solution temperature is 990°C, the solution time is 1h, the aging temperature is 600°C, and the aging time is 3h. The mechanical properties are as follows: Figure 7 , microstructure reference Figure 3 The tensile strength is 1425 Mpa, the yield strength is 1257 Mpa, and the total elongation at break is 5.10%. The microstructure consists of equiaxed α p and β-transformation structure, and martensite exists on the β-transformation structure.

[0040] Example 2 A method for preparing a high-strength and high-temperature titanium alloy comprises the following steps: Step 1. In terms of mass percentage, the mass percentage of each element is: 4.7% Al, 4.0% Sn, 3.5% Nb, 2.0% Mo, 0.5% Si, 0.15% B, and the remainder is Ti and unavoidable impurity elements.

[0041] Step 2: Use a vacuum non-consumable melting furnace for smelting. During the smelting process, argon gas is introduced. The induced current slowly increases from the starting current to 600A, and the current frequency is 22KHz. After the alloy is completely melted, the current continues to be increased to 700A. Turn on the electromagnetic stirring and maintain it for 5 minutes to ensure uniform smelting. After turning off the electromagnetic stirring, slowly reduce the current until it reaches the minimum value. After cooling, obtain an ingot, then turn the ingot over and continue smelting. The smelting number is 7, and the ingot is obtained after the smelting is completed.

[0042] Step 3: subject the ingot to high temperature homogenization heat treatment at a temperature of 1050°C for 3 hours.

[0043] Step 4: Hot-roll the homogenized ingot in the single-phase region. The hot-rolling temperature is 30°C higher than the phase transition point. After each hot-rolling pass, return to the furnace for heat preservation. The heat preservation time is 1.5 minutes. The rolling deformation is 60%, and the deformation of a single rolling pass is 7%. Then the alloy is heated to the two-phase region, that is, 50°C below the phase transition point, and the total rolling deformation is 90%. After hot rolling, it is water-cooled to room temperature. Its hot-rolled microstructure is as follows: Figure 1 and 2 As shown, β grains and equiaxed αp grains.

[0044] Step 5: subject the hot-rolled plate to solution treatment and aging treatment to obtain a near-α titanium alloy. The solution temperature is 960°C, the solution time is 1h, the aging temperature is 710°C, and the aging time is 3h. The mechanical properties are as follows: Figure 7 , microstructure reference Figure 4 The tensile strength is 1332 Mpa, the yield strength is 1252 Mpa, and the total elongation at break is 5.49%. The microstructure consists of equiaxed α p and β-transformation of tissue composition.

[0045] Example 3 A method for preparing a high-strength and high-temperature titanium alloy comprises the following steps: Step 1. In terms of mass percentage, the mass percentage of each element is: 6.5% Al, 6.0% Sn, 2.5% Nb, 1.0% Mo, 0.2% Si, 0.05% B, and the remainder is Ti and unavoidable impurity elements.

[0046] Step 2: Use a vacuum non-consumable melting furnace for smelting. During the smelting process, argon gas is introduced. The induced current is slowly increased from the starting current to 550A, and the current frequency is 20KHz. After the alloy is completely melted, the current is continued to be increased to 700A. Turn on the electromagnetic stirring for 2 minutes to ensure uniform smelting. After turning off the electromagnetic stirring, slowly reduce the current until it reaches the minimum value. After cooling, obtain an ingot, then turn the ingot over and continue smelting. The smelting number is 7, and the ingot is obtained after the smelting is completed.

[0047] Step 3: subject the ingot to high temperature homogenization heat treatment at a temperature of 1200° C. for 2 h.

[0048] Step 4: Hot-roll the homogenized ingot in the single-phase region. The hot-rolling temperature is 40°C higher than the phase transition point. After each hot-rolling pass, return to the furnace for heat preservation. The heat preservation time is 1.5 minutes. The rolling deformation is 40%, and the deformation of a single rolling pass is 10%. Then the alloy is heated to the two-phase region, that is, 30°C below the phase transition point, and the total rolling deformation is 60%. After hot rolling, it is water-cooled to room temperature. Its hot-rolled microstructure is as follows: Figure 1 As shown, β grains and equiaxed αp grains.

[0049] Step 5: subject the hot-rolled plate to solution treatment and aging treatment to obtain a near-α titanium alloy. The solution temperature is 1020°C, the solution time is 2.5h, the aging temperature is 600°C, and the aging time is 5h. The mechanical properties are as follows: Figure 7 , microstructure reference Figure 5 The tensile strength is 1386 Mpa, the yield strength is 1289 Mpa, and the total elongation at break is 7.01%. The microstructure consists of equiaxed α p and β-transformation structure, and there is incompletely decomposed martensite on the β-transformation structure.

[0050] Example 4 A method for preparing a high-strength and high-temperature titanium alloy comprises the following steps: Step 1. In terms of mass percentage, the mass percentage of each element is: 6% Al, 4.84% Sn, 3% Nb, 0.5% Mo, 0.35% Si, 0.1% B, and the remainder is Ti and unavoidable impurity elements.

[0051] Step 2: Use a vacuum non-consumable melting furnace for smelting. During the smelting process, argon gas is introduced. The induced current is slowly increased from the starting current to 500A, and the current frequency is 25KHz. After the alloy is completely melted, the current is continued to be increased to 650A. Turn on the electromagnetic stirring and keep it for 2 minutes to ensure uniform smelting. After turning off the electromagnetic stirring, slowly reduce the current until it reaches the minimum value. After cooling, obtain an ingot, then turn the ingot over and continue smelting. The smelting number is 7, and the ingot is obtained after the smelting is completed.

[0052] Step 3: subject the ingot to high temperature homogenization heat treatment at a temperature of 1100° C. for 1 h.

[0053] Step 4: Hot-roll the homogenized ingot in the single-phase region. The hot-rolling temperature is 20°C higher than the phase transformation point. After each hot-rolling pass, return to the furnace for heat preservation. The heat preservation time is 1.5 minutes. The rolling deformation is 50%, and the deformation of a single rolling pass is 7% to 10%. Then the alloy is heated to the two-phase region, that is, 40°C below the phase transformation point, and the total rolling deformation is 85%. After hot rolling, it is water-cooled to room temperature. Its hot-rolled microstructure is as follows: Figure 1 As shown, β grains and equiaxed αp grains.

[0054] Step 5: subject the hot-rolled plate to solution treatment and aging treatment to obtain a near-α titanium alloy. The solution temperature is 990°C, the solution time is 1h, the aging temperature is 680°C, and the aging time is 6h. The mechanical properties are as follows: Figure 7 , microstructure reference Figure 6 The tensile strength is 1347 Mpa, the yield strength is 1227 Mpa, and the total elongation at break is 11.31%. The microstructure consists of equiaxed α p It is composed of β-transformation structure, and there is fine and dispersed secondary α phase on the β-transformation structure.

[0055] Comparative Example 1 The ingot prepared according to the element composition of Example 1 is hot rolled from the single-phase region to the two-phase region, and water-cooled to room temperature after hot rolling, and its microstructure consists of αp + β. The difference from the preparation method of Examples 1-4 is that the solid solution aging treatment in step 5 is not performed, and only cross-phase hot rolling is performed.

[0056] According to the requirements of GB / T228.1-2010 standard, the mechanical properties of the alloy are as follows: Figure 4 For comparative example 1, the tensile strength is 1065 Mpa, the yield strength is 960 Mpa, and the total elongation at break is 16.38%. The rolled microstructure without heat treatment has average performance, good ductility but slightly insufficient strength.

[0057] Comparative Example 2 The ingot prepared according to the element composition of Example 1 was hot rolled from the single-phase region to the two-phase region, and then water-cooled to room temperature. High-temperature aging (keeping at 750°C for 2h) was directly performed without high-temperature solid solution to adjust the αp ratio. According to the requirements of GB / T228.1-2010 standard, the mechanical properties of the alloy were measured as follows: Figure 7 For comparative example 2, the tensile strength is 1171 MPa, the yield strength is 1092 MPa, and the total elongation at break is 12.43%.

[0058] This application adds Al to strengthen the α phase. Compared with the traditional high-temperature titanium alloy of Ti-Al-Sn-Zr-Mo-Si system, the addition of Zr to avoid the conflict with the surface dense oxide layer is completely eliminated, the Sn content and the weak β-stabilizing element Nb are added, and Mo, Si, and B are introduced to further improve the oxidation resistance; the extremely low solid solubility of B element and Ti is used to generate dispersed TiB intermetallic compounds, which become the heterogeneous nucleation core when β grains are transformed into α grains, reduce the formation of α phase at grain boundaries, and further reduce the microtexture in the titanium alloy. The mechanical properties of this high-temperature titanium alloy are fully strengthened by TiB and dispersed silicides. In addition, by reasonable heat treatment to control the α p The proportion of precipitation and nano-dispersion α s Compared with existing high-temperature titanium alloys and TiAl, Ti 2 AlNb intermetallic compounds achieve a more excellent match between strength and plasticity. The yield strength of the high-temperature titanium alloy is greater than 1200MPa, and it also has a ductility of 11.38%. This alloy has a tensile strength of more than 1400MPa when the martensite is not completely decomposed by heat treatment, and still has a ductility of 5%, which can further meet the current aerospace requirements for high-strength high-temperature titanium alloys.

[0059] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A high-strength and high-temperature titanium alloy, characterized in that: Calculated by mass percentage, it includes 4.7~6.5% Al, 4.0~6.0% Sn, 2.5~3.5% Nb, 0.5~2.0% Mo, 0.2~0.5% Si, 0.05~0.15% B, and the balance is Ti and unavoidable impurity elements.

2. A high-strength and high-temperature titanium alloy according to claim 1, characterized in that: The Mo is a titanium-molybdenum intermetallic compound.

3. The high-strength and high-temperature titanium alloy according to claim 1, characterized in that: The microstructure of the high-strength and high-temperature titanium alloy contains dispersed TiB particles in the form of fine needles.

4. A method for preparing a high-strength and high-temperature titanium alloy according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1, mix the elements evenly according to mass percentage; Step 2, melting the alloy mixture formed in step 1 multiple times, and obtaining an ingot after cooling; Step 3, homogenizing the ingot; Step 4, hot rolling the ingot obtained in step 3 from the single-phase region to the dual-phase region for multiple passes, with a cumulative rolling deformation of 75-90%, and cooling to room temperature after rolling; Step 5, heat treating the hot-rolled plate in a two-phase region to obtain a high-strength and high-temperature titanium alloy; The heat treatment includes solution treatment and aging treatment: The temperature of the solution treatment is 960-1020° C., the solution treatment time is 1-2.5 hours, the temperature of the aging treatment is 600-710° C., and the aging time is 3-6 hours.

5. The method for preparing a high-strength and high-temperature titanium alloy according to claim 4, characterized in that: The specific method of smelting described in step 2 is as follows: During the smelting process, the induced current is 550-700A, the current frequency is 20-25KHz, and the alloy mixture is kept for 3-5 minutes after being completely melted. After cooling, an ingot is obtained, and then the ingot is smelted multiple times.

6. The method for preparing a high-strength and high-temperature titanium alloy according to claim 4, characterized in that: The method of homogenization treatment in step 3 is as follows: The ingot is kept at 1050~1200℃ for 1~3h.

7. The method for preparing a high-strength and high-temperature titanium alloy according to claim 4, characterized in that: The method of single-phase hot rolling in step 4 is as follows: The initial rolling temperature is 20~40℃ above the phase transformation point. The steel is kept warm for 30min before rolling and returned to the furnace for insulation after each rolling pass for 1~3min. The total rolling deformation is 40~60%. The steel is cooled to room temperature after hot rolling.

8. The method for preparing a high-strength and high-temperature titanium alloy according to claim 7, characterized in that: The method of dual phase hot rolling is as follows: The rolling temperature is 30~50 ℃ below the phase transformation point, the rolling termination temperature is in the two-phase region, the furnace is returned to the furnace for insulation after each rolling pass, the insulation time is 1~3 min, and the rolling deformation is 60~90%.

9. The method for preparing a high-strength and high-temperature titanium alloy according to claim 4, characterized in that: The cooling method described in step 4 is water cooling.

10. Use of the high-strength and high-temperature titanium alloy according to any one of claims 1 to 3 in automobile and aviation engines.

Citation Information

Cited By

  • High-performance titanium alloy material capable of promoting spheroidization and preparation method of high-performance titanium alloy material

    CN121428325A

  • A high-performance titanium alloy material promoting spheroidization and a preparation method thereof

    CN121428325B